SISTEM PENDUKUNG KEPUTUSAN REKRUTMEN TENAGA KEPENDIDIKAN MENGGUNAKAN METODE PROMETHEE - Mahmudi, A. Aviv (Program Studi Teknik Informatika Universitas PGRI Ronggolawe, 2022)
Recruitment of education employees in educational institutions is an action or process of an organization's efforts to obtain additional employees for operational purposes. Universitas YPPI Rembang as one of the universities in Central Java will implement a web-based decision support system that will be used to support the decision-making process in the recruitment of lecturers and educational staff. Collecting data and information and performing analysis using the PROMETHEE method by performing numerical computations. The results of this study indicate that the PROMETHEE method can be used as a tool to determine prospective education employees. The ranking results depend on the criteria value, weight value, and preference value. The application of this method can solve the problem of selecting education employees because it is selected based on a multi-criteria ranking.